NEW TIME - NEW CHALLENGES - Lidia P. Chumakova (Высшее образование в России)
The article briefly describes the features of construction of the educational process in such monoprofile and small by modern standards university, as Novosibirsk Law Institute (branch) of Tomsk State University, the organization of students’ life at the institute, the special position of the Institute in the educational, scientific and political communities of Siberian region and the country.